2020
DOI: 10.3389/fmed.2020.00420
|View full text |Cite
|
Sign up to set email alerts
|

Secondary Bacterial Infections in Patients With Viral Pneumonia

Abstract: Pulmonary diseases of viral origin are often followed by the manifestation of secondary infections, leading to further clinical complications and negative disease outcomes. Thus, research on secondary infections is essential. Here, we review clinical data of secondary bacterial infections developed after the onset of pulmonary viral infections. We review the most recent clinical data and current knowledge of secondary bacterial infections and their treatment in SARS-CoV-2 positive patients; case reports from S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
108
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 113 publications
(121 citation statements)
references
References 82 publications
(121 reference statements)
5
108
2
Order By: Relevance
“…Pneumonia caused by viral infections usually has secondary bacterial infection 22 . COVID-19 may also be associated with secondary bacterial infections 23 , 24 .…”
Section: Discussionmentioning
confidence: 99%
“…Pneumonia caused by viral infections usually has secondary bacterial infection 22 . COVID-19 may also be associated with secondary bacterial infections 23 , 24 .…”
Section: Discussionmentioning
confidence: 99%
“…This included the occurrence of ventilator-associated pneumonia and MRSA transmission associated with remarkable increases in antimicrobial administered in the intensive care unit [ [71] , [72] , [73] ]. Besides, during the Middle East respiratory syndrome (MERS) CoV outbreak in Saudi Arabia, the most common bacteria reported among infected patients were MRSA, among others such as carbapenem-resistant Acinetobacter baumannii , Vancomycin-Resistant Enterococci and Streptococcus pneumoniae [ 74 ]. Research suggests that about half of the deaths of patients hospitalized with COVID-19 are attributable to bacterial and fungal infections some of which are resistant to antibiotics and antifungals [ 68 ].…”
Section: Resultsmentioning
confidence: 99%
“…Thus, the treatment initiated for infection (dexamethasone 6 mg/day) was based on the RECOVERY study in which this drug reduced deaths by one-third in patients who received invasive mechanical ventilation and in one-fifth of patients who received auxiliary oxygen without invasive mechanical ventilation [ 8 ]. Regarding bacterial infection, in previous pandemics, it was concluded that the co-infections, secondary infections, or “superinfections” are common during viral pandemics [ 9 ]. The 1918 Spanish Flu pandemic saw around 50 million deaths ascribed to bacterial co-infections, and during the 2009 H1N1 Influenza pandemic up to 34% of all deaths were a result of bacterial co-infections [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…Regarding bacterial infection, in previous pandemics, it was concluded that the co-infections, secondary infections, or “superinfections” are common during viral pandemics [ 9 ]. The 1918 Spanish Flu pandemic saw around 50 million deaths ascribed to bacterial co-infections, and during the 2009 H1N1 Influenza pandemic up to 34% of all deaths were a result of bacterial co-infections [ 9 ]. While the precise mechanism for susceptibility to secondary infections is unclear, it is likely that virus-mediated immunosuppression of the host innate immune enables opportunistic bacteria to colonize the host [ 9 ].…”
Section: Discussionmentioning
confidence: 99%